Increase in diagnosed asthma but not in symptoms in the European Community Respiratory Health Survey. Issue 8 (28th July 2004) - Chinn, S; Jarvis, D; Burney, P; Luczynska, C; Ackermann-Liebrich, U; Antó, J M; Cerveri, I; de Marco, R; Gislason, T; Heinrich, J; Janson, C; Künzli, N; et al.
Abstract : Background: Information on the epidemiology of asthma in relation to age is limited and hampered by reporting error. To determine the change in the prevalence of asthma with age in young adults we analysed longitudinal data from the European Community Respiratory Health Survey. Methods: A self-administered questionnaire was completed by 11 168 randomly selected subjects in 14 countries in 1991–3 when they were aged 20–44 years and 5–11 years later from 1998 to 2003. Generalised estimating equations were used to estimate net change in wheeze, nocturnal tightness in chest, shortness of breath, coughing, asthma attacks in the last 12 months, current medication, "diagnosed" asthma, and nasal allergies. Results: Expressed as change in status per 10 years of follow up, subjects reporting asthma attacks in the previous 12 months increased by 0.8% of the population (95% CI 0.2 to 1.4) and asthma medication by 2.1% (95% CI 1.6 to 2.6), while no statistically significant net change was found in reported symptoms. Reported nasal allergies increased, especially in the youngest age group. Conclusions: As this cohort of young adults has aged, there has been an increase in the proportion treated for asthma but not in the proportion of those reporting symptoms suggestive of asthma. Either increased use of effective treatments has led to decreased morbidity among asthmatic subjects or those with mild disease have become more likely to label themselves as asthmatic.